Ultra-fast and recyclable DNA biosensor for point-of-care detection of SARS-CoV-2 (COVID-19) - Hwang, Chuljin; Park, Nakkyun; Kim, Eun Seong; Kim, Miran; Kim, Su Dong; Park, Sungjun; Kim, Nam Young; Kim, Joo Hee (Biosensors and Bioelectronics, 2021)
Rapid diagnosis and case isolation are pivotal to controlling the current pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In this study, a label-free DNA capacitive biosensor for the detection of SARS-CoV-2 that demonstrates real-time, low-cost, and high-throughput screening of nucleic acid samples is presented. Our novel biosensor composed of the interdigitated platinum/titanium electrodes on the glass substrate can detect the hybridization of analyte DNA with probe DNA. The hybridization signals of specific DNA sequences were verified through exhaustive physicochemical analytical techniques such as Fourier transform infrared (FT-IR) spectrometry, contact-angle analysis, and capacitance-frequency measurements. For a single-step hybridized reaction, the fabricated kit exhibited significant sensitivity (capacitance change, ΔC = ~2 nF) in detecting the conserved region of the SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) gene with high sensitivity of 0.843 nF/nM. In addition to capacitive measurements, this selective detection was confirmed by the fluorescence image and intensity from a SARS-CoV-2 gene labeled with a fluorescent dye. We also demonstrated that the kits are recyclable by surface ozone treatment using UV irradiation. Thus, these kits could potentially be applied to various types of label-free DNA, thereby acting as rapid, cost-effective biosensors for several diseases.
Keywords: Capacitance transducers; DNA biosensors; Electrochemical DNA detection; Label free; Point of care diagnostic; Recyclable biosensor; Recyclables; Severe acute respiratory syndrome coronavirus; Severe acute respiratory syndrome coronavirus 2; Ultra-fast; Biosensing Techniques; COVID-19; DNA; Humans; Point-of-Care Systems; RNA, Viral; SARS-CoV-2; Sensitivity and Specificity; Spectroscopy, Fourier Transform Infrared; Capacitance transducer; Electrochemical DNA detection; Point-of-care diagnostics; Recyclable biosensor; SARS-CoV-2